Forest fire risk indicator (FFRI) based on geoprocessing and multicriteria analysis - Sousa, Jocy Ana Paixão de [UNESP]; Lopes, Elfany Reis do Nascimento; Duarte, Miqueias Lima [UNESP]; Ewbank, Henrique; Lourenço, Roberto Wagner [UNESP] (Springer Nature, 2022)
Forest fires negatively impact ecosystem services, affecting human welfare. The present study proposes a Forest Fire Risk Indicator (FFRI) based on the Fire and Burn Risk Indicator (FBRI). The instrument was applied to the Sorocabuçu River Basin in São Paulo State, Brazil. The FBRI was initially obtained by using the factors that most contribute to the start or spread of fires according to the literature. These factors were later grouped into anthropogenic, topographic, land cover/land use, and climatic variables. The factors of each variable were classified into intervals to which a fire risk value was assigned ranging from 0 (null risk) to 1 (very high risk). By applying the Analytical Hierarchy Process, we obtained the final FBRI, after which the FFRI was created. The final FBRI showed predominantly high risks (64.78%) throughout the basin, as well as the FFRI (82.56%). The present study evidences that most forest fragments need measures for ecosystem protection. This can be done in different ways such as monitoring through fire towers and conduction of environmental education activities.
Keywords: Fire outbreaks; Fire susceptibility; Forest ecosystems; Forest loss